2014
DOI: 10.7314/apjcp.2014.15.17.7207
|View full text |Cite
|
Sign up to set email alerts
|

Primary Extranodal Non-Hodgkin's Lymphoma: Clinicopathological Features, Survival and Treatment Outcome in Two Cancer Centers of Southern Turkey

Abstract: Background: The aim of this study was to assess the epidemiological and clinicopathological characteristics of primary extranodal non-Hodgkin's lymphoma (pENL) patients, focusing on treatment and survival outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Male preponderance with M:F ratio of 2.1:1 observed and is comparable to various studies reported in literature. [1,2,10] Also all the 25 cases of ENHL were immunocompetent and had no B symptoms, but however presented with signs and symptoms pertaining to location.…”
Section: Discussionmentioning
confidence: 99%
“…Male preponderance with M:F ratio of 2.1:1 observed and is comparable to various studies reported in literature. [1,2,10] Also all the 25 cases of ENHL were immunocompetent and had no B symptoms, but however presented with signs and symptoms pertaining to location.…”
Section: Discussionmentioning
confidence: 99%
“…The most common histology seen in literature is DLBCL followed by Marginal Zone Lymphomas (MZL) (Wotherspoon AC et al, 1993;Mertsoylu H, 2014). In The current study DLBCL was the most common histological subtype, followed by follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Th ere are confl icting reports in the literature regarding involvement of the most common systems and sites. However most of the studies report gastrointestinal tract as the most common system involved followed by head and neck and central nervous system (CNS) [5,6,9,18,[20][21][22][23][24][32][33][34] . Bone, testis, thyroid, breast, orbit, skin, rarely adrenal glands, pancreas, and the genitourinary tract are among the other frequent sites [5,6,9,18,[20][21][22][23][24][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%